Difference Strategy Analysis Which Influences On Competitive Advantage In The Hotel Industry Around Danau Toba - Siahaan, Djames (Green Publisher Indonesia, 2023)
This study examines the relationship between the Differentiation Strategy that has been implemented by the Melati Ш Hotel industry around Danau Toba and Competitive Advantage. The researcher proposes a conceptual framework in which the sources of Differentiation consisting of Price, Service, Size Promotion and Location are linked to Competitive Advantage. The Competitive Advantage gained by the Budget Hotel industry Ш Around Danau Toba is measured based on the occupancy rate. The empirical test uses the Multiple Regression Analysis method which is supported by an analysis of the competitive environment. The results of the study show that the variables of price, service, promotion and location have a significant effect on Competitive Advantage. While the size variable has no significant effect. Based on the analysis of Partial Determination, the results show that the factor that most influences competitive advantage is price with a coefficient of determination of 0.922. By understanding the importance of a Differentiation Strategy, Hotel Melati Ш can create a difference with its competitors, so that it is able to compete in a more competitive market. The results of the analysis show that in the Budget Hotel industry Ш there are several hotels that apply the Differentiation strategy. With this research, Hotel Melati Ш, which has differentiated itself from competitors, can further emphasize and communicate its differences